ANALISIS ISLAMIC CORPORATE GOVERNANCE DAN ISLAMIC CORPORATE SOCIAL RESPOSIBILITY DALAM DISIPLIN PASAR PERBANKAN SYARIAH DI INDONESIA - hartono, nono (UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
The objectives of this study are determine the effect of Islamic Corporate Governance (ICG) and Islamic Corporate Social Responsibility (ICSR) on market discipline with financial performance as an intervening variable. The ICG and ICSR disclosures is measured from the disclosure score compiled based of IFSB standard, AAOIFI, and relevant previous research. Market discipline measured by the ratio of deposit growth. While financial performance measured by profitability ratios in ROA and ROE. The sample used 11 Islamic banks in Indonesia were selected using purposive sampling method. Empirical testing uses the method of Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of content analysis on the sharia bank information reports for the period 2013-2015 show that the level of ICG and ICSR disclosure is quite good, namely 62% and 60% respectively. The empirical test was proved that ICG and ICSR disclosures have a positive and significant effect on market discipline. Financial performance is not able to be an ICG and ICSR liaison variable to the market discipline of Islamic banks significant direct effect on the market discipline of Islamic banks. Financial performance has’nt significant on market discipline, and that is’nt being intervening variabels to the market discipline of Islamic banks.